2022
DOI: 10.31219/osf.io/xm8ns
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain-heart interactions in the neurobiology of consciousness

Abstract: Recent experimental evidence on patients with disorders of consciousness revealed that observing brain-heart interactions helps to detect residual consciousness, even in patients with absence of behavioral signs of consciousness. Those findings support hypotheses suggesting that visceral activity is involved in the neurobiology of consciousness, and sum to the existing evidence in healthy participants in which the neural responses to heartbeats reveal perceptual and self-consciousness. More evidence obtained t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 159 publications
1
9
0
Order By: Relevance
“…The study of mental stress elicited in other paradigms, such as mental arithmetic, could give a broader view of the physiological processes involved in brain–heart information exchange. Our study confirms the advantages of analyzing the interactions between brain and heart, instead of studying heart rate and brain dynamics separately [19,67], to understand the origin and potential pathways of the observed physiological changes. The understanding of brain–heart dynamics and the neurophysiological substrates of stress has clinical relevance.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The study of mental stress elicited in other paradigms, such as mental arithmetic, could give a broader view of the physiological processes involved in brain–heart information exchange. Our study confirms the advantages of analyzing the interactions between brain and heart, instead of studying heart rate and brain dynamics separately [19,67], to understand the origin and potential pathways of the observed physiological changes. The understanding of brain–heart dynamics and the neurophysiological substrates of stress has clinical relevance.…”
Section: Discussionsupporting
confidence: 78%
“…The existing EEG evidence is described as neural correlates, which does not imply causality between the observed parallel changes in brain and autonomic activities [19]. For instance, acute stress triggers parallel fluctuations in heart rate variability and functional connectivity between central executive and default mode networks [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there has been a substantial increase in the number of studies on interoception that aim to describe the mechanisms involved in the sensing of inner bodily signals and their influence on brain dynamics. [1][2][3] Interoception includes the sensing of cardiac, respiratory, and gut signaling. 4 More in general, interoception has been defined as the sense of physiological condition of the entire body, 5 which can potentially include other interoceptive submodalities, such as thermosensation, pain, or affective touch.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] The functions associated with interoceptive processes include homeostatic and allostatic regulation as well as the integration of information that enables bodily awareness and consciousness. 1,3,[10][11][12][13] Evidence has demonstrated that neural responses to heartbeats contribute to visual, 14 somatosensory, 15 auditory, 16,17 and self-perception. [18][19][20] Further, recent evidence has suggested that breathing is aligned with the perception of sensory inputs, 21,22 suggesting that it is involved in perceptual sensitivity modulation and, possibly, shaping neural dynamics.…”
Section: Introductionmentioning
confidence: 99%